Cultural Expertise and Law: An Historical Overview. (February 2020) - Holden, Livia
Abstract : The use of anthropology and sociology for dispute resolution, law-making, and governance has been frequent throughout the history of law and anthropology. Anthropological expertise in the form of expert witnessing or expert information, has been one among the significant activities of applied anthropology. However, no concept such the one of cultural expertise was formulated to theorise the engagement of anthropologists and sociologists with law. This paper adopts an historical approach in order to understand why socio-legal studies have not developed a conceptualisation that encompasses the variety of the types of engagement of social scientists, and anthropologists in particular. It investigates the connection between law and culture in the history of anthropology of law since social evolutionism, and focuses in particular on legal pluralism. This paper suggests that the reasons for the late conceptualisation of cultural expertise lies on the one hand in the difficulty to define the dynamics between law and culture, and on the other hand in the specific development of legal pluralism vis-à-vis the state. This paper concludes with a reformulation of the concept of cultural expertise as an umbrella concept that encompasses the existing array of socio-legal instruments that use cultural knowledge for conflict resolution.